2015
DOI: 10.1128/jcm.02072-15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV Infection Status on Interpretation of Quantitative PCR for Detection of Pneumocystis jirovecii

Abstract: Quantitative PCR (qPCR) is now a key diagnostic tool forPneumocystispneumonia. However, cutoffs to distinguish between infected and colonized patients according to their HIV status have not yet been determined. According to clinical, radiological, and biological data, we retrospectively classified bronchoalveolar lavage (BAL) samples subjected to qPCR over a 3-year period into four categories, i.e., definite PCP, probable PCP,Pneumocystiscolonization, and no infection. Fungal burden was then analyzed according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 33 publications
3
31
1
1
Order By: Relevance
“…Various other targets like ITS, DHPS, DHFS, β-tubulin and mtLSU had been studied in the past. Although mtLSU has been the most popular target, 16,20 studies have shown that the MSG gene has higher sensitivity for PJ. 29,30 A recent study further supports our chosen target by exposing the variability in the copy number of the mtLSU gene that fluctuates widely according to the physiological state of PJ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various other targets like ITS, DHPS, DHFS, β-tubulin and mtLSU had been studied in the past. Although mtLSU has been the most popular target, 16,20 studies have shown that the MSG gene has higher sensitivity for PJ. 29,30 A recent study further supports our chosen target by exposing the variability in the copy number of the mtLSU gene that fluctuates widely according to the physiological state of PJ.…”
Section: Discussionmentioning
confidence: 99%
“…Although conventional PCR can improve sensitivity of detection, it cannot differentiate the disease from colonisation in the absence of quantification. These challenges have been addressed with various real‐time quantitative PCRs, using different target genes and methodologies . The interpretation of these qPCRs, however, remain confusing owing to several contrasting variables thereby hindering reliable fungal burden estimation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis of AIDS-related PCP rests on the identification of cystic or trophic forms of P. jirovecii trough staining and/or immunofluorescence on BAL fluid, which have a > 90% sensitivity and a ~ 100% specificity in patients with a clinical presentation and a CD4 cell count compatible with this condition (Table 1) [54,58]. The detection of P. jirovecii DNA by polymerase chain reaction (PCR) in BAL fluid is highly sensitive but poorly specific in HIV-infected patients due to a high prevalence of colonization (up to 70%) in patients with low CD4 cell counts [59][60][61]. Serum ß-D-glucan (cut-off level, 80 pg/ mL) is also sensitive (> 92%) yet lacks specificity (78-82%) as the test may be positive in other AIDS-related OIs such as invasive candidiasis or histoplasmosis [62,63].…”
Section: Common Aids-defining Diagnoses In the Icumentioning
confidence: 99%
“…The use of quantitative methods has been necessary in order to discriminate between colonization and disease; thus, at least partially overcoming the problem of false-positive results. Although promising, the cut-off values remain to be standardized for quantitative NATs and may vary with patient population [46].…”
Section: Pneumocystis Jiroveciimentioning
confidence: 99%